A red light LED epitaxial wafer and preparation method thereof

By introducing an antioxidant DBR reflection layer, an N-plane/P-plane micro-strain layer and a P-type cyclic doping restriction layer into the red LED epitaxial structure, the problem of brightness attenuation of red LEDs under high temperature, high humidity and high current conditions is solved, and higher stability and reliability are achieved.

CN119403314BActive Publication Date: 2025-04-22NANCHANG KAIXUN PHOTOELECTRIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510000123.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-22
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

Existing red LEDs are prone to problems such as attenuation of luminance, decreasing adhesion and chip aging under high temperature and high humidity environments and high current conditions.

Method used

The antioxidant DBR reflection layer, an N-plane/P-plane micro-strain layer and a P-type cyclic doping restriction layer are introduced into the red LED epitaxial structure. The stability and reliability of the chip are improved through Si/Te co-doped AlAs material and periodic cyclic doping structure.

Benefits of technology

It effectively prevents DBR reflective layer from being damp and oxidized in humid environments, inhibits the diffusion of Mg elements, improves luminous efficiency and brightness stability, and extends the service life of LED chips.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403314B_ABST
    Figure CN119403314B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of LED technology, and in particular to a red light LED epitaxial wafer and a preparation method thereof. The red light LED epitaxial wafer comprises, from bottom to top, a GaAs substrate, a GaAs buffer layer, an anti-oxidation DBR reflective layer, an N-type confinement layer, an N-side micro-strain layer, an N-side space layer, a multi-quantum well active layer, a P-side space layer, a P-side micro-strain layer, a P-type cyclic doping confinement layer, a P-type transition layer, and a P-type window layer. The present invention adjusts the conventional DBR reflective layer material to an anti-oxidation DBR reflective layer, introduces Al into the P-type confinement layer, and converts the conventional DBR reflective layer material into an anti-oxidation DBR reflective layer. 0.5 In 0.5 P:C / Al 0.5 In 0.5 The P:Mg periodic doping structure can effectively solve the problems of light efficiency attenuation and brightness attenuation of conventional red LEDs in high temperature and high humidity environments or under high current conditions. The obtained red LED epitaxial wafer has good light efficiency stability, high reliability and wide applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of LEDs, and in particular to a red light LED epitaxial wafer and a preparation method thereof. Background Art

[0002] As a semiconductor solid-state light-emitting device, LED can directly convert electrical energy into light energy. It has the advantages of low power consumption, long life, small size, energy saving and environmental protection. In particular, with the maturity of metal organic chemical vapor deposition (MOCVD) epitaxial growth technology, red LEDs represented by quaternary aluminum gallium indium phosphide (AlGaInP) materials have developed rapidly and have been commercialized on a large scale. They have been widely used in display screens, interior decoration, outdoor lighting, traffic lights and other fields. The temperature characteristics of red LEDs are a key parameter for reliable performance. At high temperatures, the internal thermal motion of LEDs intensifies, resulting in the escape and diffusion of carriers, affecting the probability of radiative recombination of carriers, thereby reducing the luminous efficiency and brightness of red LEDs. In a high humidity environment, the oxidation of the epitaxial material of the LED chip will accelerate the aging of the device and reduce reliability. Therefore, it is of great significance to prepare high-temperature and high-humidity resistant high-reliability red LEDs.

[0003] At present, the schematic diagram of the conventional red LED epitaxial structure is as follows Figure 1 As shown, from bottom to top, it includes GaAs substrate 1, GaAs buffer layer 2, DBR reflective layer 3-1, N-type confinement layer 4, N-side space layer 5, multi-quantum well active layer 6, P-side space layer 7, P-type confinement layer 8-1, P-type transition layer 9, and P-type window layer 10. In the existing conventional red light LED structure, the DBR (distributed Bragg reflector) structure layer is generally a periodic structure of AlAs / AlGaAs alternating growth. When used in outdoor display screens or humid environments, it is easy to react with moisture and oxidation in the AlAs material layer with a high Al content due to high temperature and humidity. During continuous lighting, the oxidation of the AlAs layer will cause the adhesion between the DBR reflective layers to decrease, or cause severe local heating of the chip, thereby causing severe attenuation of the luminous brightness or dimming, affecting normal use. At the same time, the AlInP material on the P-type side of the existing conventional red light LED structure generally uses Mg as a dopant. As the size of the LED chip becomes smaller and smaller, the current density increases under the same working current state, and the heat generation of the chip in the working state will gradually become more serious. The influence of the thermal effect will intensify the diffusion of the Mg element into the quantum well, forming non-radiative composite impurity energy levels, causing serious aging of the chip during normal operation and attenuation of the luminous efficiency. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a red light LED epitaxial wafer and a method for preparing the same. By introducing an anti-oxidation DBR reflective layer, an N-side / P-side micro-strain layer, and a P-type cyclic doping restriction layer into the red light LED epitaxial structure, the stability and reliability of the chip in high temperature and high humidity environments and high current working conditions can be improved, and problems such as luminous brightness attenuation or failure under harsh conditions can be improved.

[0005] The first object of the present invention is to provide a red light LED epitaxial wafer, which comprises, from bottom to top, a GaAs substrate, a GaAs buffer layer, an anti-oxidation DBR reflective layer, an N-type confinement layer, an N-side micro-strain layer, an N-side space layer, a multi-quantum well active layer, a P-side space layer, a P-side micro-strain layer, a P-type cyclically doped confinement layer, a P-type transition layer, and a P-type window layer;

[0006] The anti-oxidation DBR reflective layer is AlAs / Al x1 Ga 1-x1 As alternately grows in a periodic cycle structure, and in each pair of periodic cycle structures, AlAs is co-doped with Si / Te. x1 Ga 1-x1 As is doped with Si, where the value of x1 ranges from 0.4 to 0.6.

[0007] The Te element has good corrosion resistance and oxidation resistance, and acts as an N-type dopant while also acting as an oxidation inhibitor. The present invention adjusts the conventional DBR reflective layer material to an anti-oxidation DBR reflective layer structure, and by designing the material of the anti-oxidation DBR reflective layer into a periodic structure of alternating growth of AlAs / AlGaAs, and using Si / Te co-doping in the AlAs material, the DBR reflective layer of the red light LED can be effectively prevented from being oxidized by moisture in a humid environment, and the adhesion stability and reliability between the epitaxial materials are improved, while ensuring the conductivity in a high temperature and high humidity environment, and avoiding the problem of light efficiency attenuation. In addition, the present invention introduces a periodic cyclic doping structure in the P-type confinement layer, which can inhibit the diffusion of Mg elements into the active area, and solve the problem of brightness attenuation under high temperature operation and high current density. At the same time, the N-face / P-face micro-strain layer material is inserted outside the space layer on both sides, which can not only compensate for the compressive strain of the quantum well under high temperature and high current working conditions in the form of tensile strain, but also block the diffusion problem of the P-face Mg element in the high temperature and high pressure packaging process, thereby solving the leakage or light decay problem of the conventional red light LED chip after high temperature baking and reflow soldering during the packaging process.

[0008] Furthermore, in the Si / Te co-doped anti-oxidation DBR reflective layer AlAs material, the Si dopant is SiH4 (monosilane) with a doping concentration of 2×10 18 cm -3 ~3×10 18cm -3 ; The dopant of Te is DETe (diethyltellurium) with a doping concentration of 0.5×10 18 cm -3 ~1×10 18 cm -3 ;Al x1 Ga 1-x1 In As material, the dopant of Si is SiH4, and the doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 In this technical solution, the AlAs material is co-doped with Si / Te, and Te is used as an oxidation inhibitor, which can improve the oxidation phenomenon of the DBR reflective layer of the LED chip in a humid environment, improve the adhesion of the epitaxial layer, prevent it from falling off, and improve the reliability of the LED chip device.

[0009] Furthermore, the material of the P-type cyclic doping limiting layer is Al 0.5 In 0.5 P, the cyclic doping method is to first dope organically and then dope metals to form Al 0.5 In 0.5 P:C / Al 0.5 In 0.5 The periodic cyclic doping structure of alternating growth of P:Mg has a cycle number of 10 to 15 pairs. In this technical solution, the P-type confinement layer adopts a periodic cyclic doping structure, which can not only ensure that sufficient P-type carriers participate in the composite luminescence, but also inhibit the diffusion of Mg elements at high temperatures through the intermediate C doping layer, thereby improving the light efficiency stability and reliability under high temperature operation and high current density.

[0010] Furthermore, in each pair of periodic cyclic doping structures, Al 0.5 In 0.5 The organic dopant used in P:C is CCl4 (carbon tetrachloride), and the doping concentration is 0.5×10 18 cm -3 ~1×10 18 cm -3 , thickness is 5nm~10nm; Al 0.5 In 0.5 The metal dopant used in P:Mg is Cp2Mg (bismuth magnesium) with a doping concentration of 1×10 18 cm -3 ~2×10 18 cm -3 , thickness is 10nm~20nm.

[0011] Furthermore, the materials of the N-face microstrain layer and the P-face microstrain layer are both AlGaInP, and both are non-doped, the molar amount of the Al source material is x, and the molar amount of the Ga source material is y, wherein the total molar amount of x and y, x+y, is 140μmol-150μmol, and y=a*x, and the coefficient a is 0.07. In this technical solution, the N-face / P-face microstrain layer material can adjust the lattice size of the microstrain layer by increasing the total Al / Ga content and keeping the Al / Ga molar ratio unchanged, thereby adjusting the strain state to tensile stress, thereby compensating the stress of the quantum well active area, and improving the problems of crystal quality and increased defect density resulting in brightness attenuation due to excessive compressive strain of the quantum well in the high-temperature and high-pressure packaging process and reflow soldering process.

[0012] Furthermore, the thickness of the N-side micro-strain layer is 40nm-60nm, and the thickness of the P-side micro-strain layer is 70nm-90nm.

[0013] The second object of the present invention is to provide a method for preparing a red light LED epitaxial wafer, using MOCVD equipment to sequentially grow a GaAs buffer layer, an anti-oxidation DBR reflective layer, an N-type confinement layer, an N-side micro-strain layer, an N-side space layer, a multi-quantum well active layer, a P-side space layer, a P-side micro-strain layer, a P-type cyclically doped confinement layer, a P-type transition layer, and a P-type window layer on a GaAs substrate;

[0014] When the anti-oxidation DBR reflective layer is grown, Si / Te co-doped AlAs material is first grown, and then Si-doped AlGaAs material is grown to complete the first anti-oxidation DBR reflective layer, and then 14 to 19 pairs of growth cycles are repeated;

[0015] When the P-type cyclic doping restriction layer grows, the organic doping layer Al is first grown. 0.5 In 0.5 P:C, then grow the metal doping layer Al 0.5 In 0.5 P:Mg forms the first pair of cyclic doping confinement layers, and then the cycle is repeated to grow 9 to 14 pairs.

[0016] Furthermore, the growth step of the anti-oxidation DBR reflective layer is as follows: setting the reaction chamber temperature to 700±20°C, introducing TMAl, AsH3, SiH4 and DETe as dopants on the GaAs buffer layer, growing AlAs material with a thickness of 45nm to 50nm, wherein the set flow rate of SiH4 is 80sccm to 110sccm, and the set flow rate of DETe is 20sccm to 40sccm, then turning off DETe, introducing TMGa and SiH4 as dopants, and growing AlAs with a thickness of 60nm to 65nm. x1 Ga 1-x1As material, and then repeated cycle growth AlAs / Al x1 Ga 1-x1 As, where the value range of x1 is 0.4 to 0.6.

[0017] Furthermore, the growth steps of the N-side microstrain layer and the P-side microstrain layer are the same: setting the reaction chamber temperature to 700±20°C, introducing TMAl, TMGa, TMIn, and PH3 into the N-type confinement layer or the P-side space layer to grow AlGaInP material, the molar amounts of the Al source material and the Ga source material are x and y, respectively, wherein the total molar amount x+y of x and y is 140μmol~150μmol, and y=a*x, and the coefficient a is 0.07.

[0018] Furthermore, the P-type cyclic doping restriction layer growth step is: setting the reaction chamber temperature to 730±20°C, introducing TMAl, TMIn, and PH3 on the P-side micro-strain layer, and growing Al 0.5 In 0.5 P material, CCl4 is used as the dopant of the organic doping layer, the flow rate is set to 5sccm~10sccm, then CCl4 is turned off, Cp2Mg is introduced as the dopant of the metal doping layer, the flow rate is set to 60sccm~80sccm, and the cycle is repeated to grow Al 0.5 In 0.5 P:C / Al 0.5 In 0.5 P:Mg.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention adjusts the conventional DBR reflective layer material to an anti-oxidation DBR reflective layer structure. The AlAs material of the DBR reflective layer adopts Si / Te co-doping, and Te is used as an oxidation inhibitor to obtain an AlAs material with anti-oxidation ability. This can not only improve the moisture oxidation phenomenon of the DBR reflective layer of the LED chip in a humid environment, improve the adhesion stability and reliability of the epitaxial layer, but also ensure the conductivity in a high temperature and high humidity environment, avoiding the problem of light efficiency attenuation.

[0021] 2. The present invention introduces Al into the P-type confinement layer 0.5 In 0.5 P:C / Al 0.5 In 0.5The P:Mg periodic cyclic doping structure, the prepared red light LED is used in high temperature or high current scenarios, which can effectively inhibit the diffusion of Mg elements into the active area, improve the light efficiency stability and reliability under high temperature operation and high current density, and solve the problem of brightness attenuation. At the same time, the N-face / P-face micro-strain layer material is inserted outside the space layer on both sides. By increasing the total content of Al / Ga and keeping the molar ratio of Al / Ga unchanged, the lattice size of the micro-strain layer can be adjusted to adjust the strain state to tensile stress, so as to compensate the stress of the quantum well active area, and at the same time, it can also block the diffusion of Mg elements on the P-face during the high temperature and high pressure packaging process, further solving the brightness attenuation problem of conventional red light LED chips after high temperature baking and reflow soldering during the packaging process.

[0022] 3. The red LED epitaxial wafer obtained by the present invention not only effectively solves the problems of light efficiency attenuation and brightness attenuation of conventional red LEDs in high temperature and high humidity environments or under high current conditions, but also ensures the stability and reliability of the epitaxial wafer performance and has wide applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a schematic diagram of the structure of a conventional red LED epitaxial wafer;

[0024] Figure 2 This is a schematic diagram of the structure of a red LED epitaxial wafer of the present invention;

[0025] Figure 3 These are images taken with a conventional red light LED scanning electron microscope; (a) is a SEM image of the LED exterior, and (b) is a SEM image of the LED internal cutting layer;

[0026] Figure 4 The red light LED of the present invention is photographed by a scanning electron microscope; (a) is a SEM image of the LED appearance, and (b) is a SEM image of the LED internal cutting layer.

[0027] Description of the numbers in the schematic diagram:

[0028] 1. GaAs substrate; 2. GaAs buffer layer; 3-1. DBR reflective layer; 3-2. Anti-oxidation DBR reflective layer; 4. N-type confinement layer; 5. N-side space layer; 6. Multi-quantum well active layer; 7. P-side space layer; 8-1. P-type confinement layer; 8-2. P-type cyclic doping confinement layer; 9. P-type transition layer; 10. P-type window layer; 11. N-side microstrain layer; 12. P-side microstrain layer. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application or use. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] In the description of the present application, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present application.

[0031] In the description of the present application, it should be understood that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the scope of protection of the present application; the directional words "inside and outside" refer to the inside and outside relative to the contours of each component itself.

[0032] See also Figures 1 to 4 It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and therefore the illustrations only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the form, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0033] A red LED epitaxial wafer is provided in one embodiment of the present invention, and its structural schematic diagram is as follows: Figure 2 As shown, from bottom to top, it includes GaAs substrate 1, GaAs buffer layer 2, anti-oxidation DBR reflective layer 3-2, N-type confinement layer 4, N-face micro-strain layer 11, N-side space layer 5, multi-quantum well active layer 6, P-side space layer 7, P-face micro-strain layer 12, P-type cyclic doping confinement layer 8-2, P-type transition layer 9, and P-type window layer 10.

[0034] In some embodiments, the doping material of the GaAs buffer layer is SiH4 with a doping concentration of 3×10 18 cm -3 ~5×10 18 cm -3, with a thickness of 200nm~300nm.

[0035] In some embodiments, the oxidation resistant DBR reflective layer is AlAs / Al x1 Ga 1-x1 As alternately grows in a periodic cycle structure, and the number of cyclic pairs of AlAs and AlGaAs alternately grows is 15 to 20 pairs. The thickness of AlAs in each periodic cycle structure is 45nm to 50nm, and the thickness of AlGaAs is 60nm to 65nm. In each pair of periodic cycle structures, AlAs is co-doped with Si / Te, and Al x1 Ga 1-x1 As is doped with Si, where the value of x1 ranges from 0.4 to 0.6.

[0036] Furthermore, in the Si / Te co-doped anti-oxidation DBR reflective layer AlAs material, the Si dopant is SiH4 with a doping concentration of 2×10 18 cm -3 ~3×10 18 cm -3 ; The dopant of Te is DETe, and the doping concentration is 0.5×10 18 cm -3 ~1×10 18 cm -3 ;Al x1 Ga 1-x1 In As material, the dopant of Si is SiH4, and the doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 The AlAs material of the DBR reflective layer is co-doped with Si / Te, and Te is used as an oxidation inhibitor, which can improve the oxidation phenomenon of the DBR reflective layer of the LED chip in a humid environment, improve the adhesion of the epitaxial layer, prevent it from falling off, and improve the reliability of the LED chip device.

[0037] In some embodiments, the N-type confinement layer material is Al 0.5 In 0.5 P, doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 , the doping material is Si and the thickness is 300nm~400nm.

[0038] In some embodiments, the materials of the N-side microstrain layer and the P-side microstrain layer are both AlGaInP, and both are undoped, the thickness of the N-side microstrain layer is 40nm-60nm, the thickness of the P-side microstrain layer is 70nm-90nm, the molar amounts of the Al source material and the Ga source material are x and y, respectively, wherein the total molar amount of x and y x+y is 140μmol-150μmol, and y=a*x, and the value of the coefficient a is 0.07. The N-side microstrain layer / P-side microstrain layer material is inserted outside the space layer on both sides of the LED, and the strain state of the tensile strain layer is adjusted to tensile stress by increasing the total Al / Ga content but keeping the molar ratio of Al / Ga unchanged, which is used to compensate for the excessive compressive strain of the multi-quantum well active layer during the high-temperature and high-pressure packaging process, further improving the brightness attenuation problem.

[0039] In some embodiments, the multi-quantum well active layer has 20 to 30 pairs of quantum well / barrier structures, wherein the materials of the quantum well layers / barrier layers are all AlGaInP; specifically, the material of the quantum well layer is (Al x2 Ga 1-x2 ) 0.5 In 0.5 P, the thickness of the single-layer quantum well is 6nm~8nm, the value range of x2 is 0.06~0.07; the material of the quantum barrier layer is (Al x3 Ga 1-x3 ) 0.5 In 0.5 P, the thickness of a single-layer quantum barrier is 8nm to 10nm, and the value range of x3 is 0.7 to 0.8; both the quantum well and the quantum barrier are non-doped.

[0040] In some embodiments, the materials of the N-side space layer and the P-side space layer are (Al x3 Ga 1-x3 ) 0.5 In 0.5 P, and both are non-doped. Among them, the thickness of the N-side space layer is 50nm~100nm, the thickness of the P-side space layer is 50nm~100nm, and the value range of x3 is 0.7~0.8.

[0041] In some embodiments, the material of the P-type cyclic doping confinement layer is Al 0.5 In 0.5 P, the cyclic doping method is to first dope organically and then dope metals to form Al 0.5 In 0.5 P:C / Al 0.5 In 0.5 The periodic cyclic doping structure composed of P:Mg alternating growth has a cycle number of 10 to 15 pairs. In each pair of periodic cyclic doping structure, Al 0.5 In 0.5The organic dopant used in P:C is CCl4, and the doping concentration is 0.5×10 18 cm -3 ~1×10 18 cm -3 , thickness is 5nm~10nm; Al 0.5 In 0.5 The metal dopant used in P:Mg is Cp2Mg, and the doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 , with a thickness of 10nm to 20nm. The P-type confinement layer adopts a periodic cyclic doping structure, which can not only ensure sufficient P-type carriers to participate in the composite luminescence, but also inhibit the diffusion of Mg elements to the active area at high temperatures through the intermediate C doping layer, thereby improving the light efficiency stability and reliability under high temperature operation and high current density.

[0042] In some embodiments, the material of the P-type transition layer is (Al x4 Ga 1-x4 ) 0.5 In 0.5 P, thickness is 10nm~20nm, dopant is Cp2Mg, doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 , the value range of x4 is 0.3~0.4.

[0043] In some embodiments, the material of the P-type window layer is GaP, the thickness is 4000nm to 5000nm, the dopant is CP2Mg, and the doping concentration is 2×10 18 cm -3 ~3×10 18 cm -3 .

[0044] In another embodiment, the present invention also provides a method for preparing a red light LED epitaxial wafer, using MOCVD equipment to sequentially grow a GaAs buffer layer, an anti-oxidation DBR reflective layer, an N-type confinement layer, an N-side micro-strain layer, an N-side space layer, a multi-quantum well active layer, a P-side space layer, a P-side micro-strain layer, a P-type cyclic doping confinement layer, a P-type transition layer, and a P-type window layer on a GaAs substrate. Specifically, the following steps are included:

[0045] (1) The MOCVD was evacuated to 50 mbar in a pure H2 atmosphere, and the reaction chamber temperature was set to 400°C. The GaAs substrate was then transferred to the reaction chamber through a robot transfer bin, and then the temperature was rapidly raised to 750°C and maintained at a constant temperature of 750°C for 10 min to 15 min.

[0046] (2) Growth of GaAs buffer layer: The reaction chamber temperature was set to 700±20℃, TMGa and AsH3 were introduced, and GaAs buffer layer material with a thickness of 200nm to 300nm was grown. SiH4 was used as the N-type dopant with a doping concentration of 3×10 18 cm -3 ~5×10 18 cm -3 .

[0047] (3) Growth of oxidation-resistant DBR reflective layer: The reaction chamber temperature was set to 700±20℃, TMAl and AsH3 were introduced, SiH4 and DETe were introduced as N-type co-dopants, and AlAs material with a thickness of 45nm to 50nm was grown. The flow rate of SiH4 was set to 80sccm to 110sccm, and the doping concentration was 2×10 18 cm -3 ~3×10 18 cm -3 The flow rate of DETe was set to 20 sccm to 40 sccm, and the doping concentration was 0.5×10 18 cm -3 ~1×10 18 cm -3 Then turn off DETe and introduce TMGa to grow Al with a thickness of 60nm to 65nm x1 Ga 1-x1 As material, dopant is SiH4, doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 , x1 ranges from 0.4 to 0.6. x1 Ga 1-x1 As growth combination forms the first anti-oxidation DBR reflective layer, and then the cycle is repeated for 14 to 19 pairs of the combined structure.

[0048] (4) Growth of N-type confinement layer: Set the reaction chamber temperature to 700±20℃, introduce TMAl, TMIn, and PH3, and grow Al with a thickness of 300nm to 400nm. 0.5 In 0.5 P, doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 , the N-type dopant is SiH4.

[0049] (5) Growth of N-side microstrain layer: Set the temperature of the reaction chamber to 700±20℃, introduce TMGa, TMAl, TMIn, and PH3, and grow AlGaInP material with a thickness of 40nm to 60nm. The total molar amount x+y of the molar amount of Al source x and the molar amount of Ga source y in the N-side microstrain layer is 140μmol to 150μmol, and y=a*x, and the coefficient a is 0.07; the N-side microstrain layer is non-doped.

[0050] (6) Growth of N-side space layer: Set the temperature of the reaction chamber to 700±20℃, introduce TMGa, TMAl, TMIn, and PH3, and grow (Al) with a thickness of 50nm to 100nm. x3 Ga 1-x3 ) 0.5 In 0.5 P material, wherein the value of x3 ranges from 0.7 to 0.8; the N-side space layer is undoped.

[0051] (7) Growth of multi-quantum well active layer: Set the temperature of the reaction chamber to 700±20℃, introduce TMGa, TMAl, TMIn, and PH3, and grow quantum well layer and quantum barrier layer respectively (Al x2 Ga 1-x2 ) 0.5 In 0.5 P、(Al x3 Ga 1-x3 ) 0.5 In 0.5 P material, wherein the thickness of a single-layer quantum well is 6nm to 8nm, the value range of x2 is 0.06 to 0.07, the thickness of a single-layer quantum barrier is 8nm to 10nm, and the value range of x3 is 0.7 to 0.8; the number of periods is 20 pairs to 30 pairs, and the light-emitting region is non-doped;

[0052] (8) Growth of P-side space layer: Set the temperature of the reaction chamber to 700±20℃, introduce TMGa, TMAl, TMIn, and PH3, and grow (Al) with a thickness of 50nm to 100nm. x3 Ga 1-x3 ) 0.5 In 0.5 P material, wherein the value range of x3 is 0.7 to 0.8; the P-side space layer is undoped.

[0053] (9) Growth of P-face microstrain layer: Set the temperature of the reaction chamber to 700±20℃, introduce TMGa, TMAl, TMIn, and PH3, and grow AlGaInP material with a thickness of 40nm to 60nm. The total molar amount x+y of the Al source molar amount x and the Ga source molar amount y of the P-face microstrain layer is 140μmol to 150μmol, and y=a*x, and the coefficient a is 0.07; the P-face microstrain layer is non-doped.

[0054] (10) Growth of P-type cyclic doping confinement layer: Set the temperature of the reaction chamber to 730±20℃, introduce TMAl, TMIn, and PH3 to grow Al 0.5 In 0.5 P material is used as P-type cyclic doping limiting layer. First organic doping and then metal doping, Al 0.5 In 0.5 P:C (organic doping layer) / Al 0.5 In 0.5 P:Mg (metal doping layer) grows alternately to form a periodic cyclic doping confinement layer, and the number of pairs of cycles is 10 to 15 pairs. In a single cyclic doping structure, the organic doping layer Al 0.5 In 0.5 The thickness of P:C is 5nm~10nm, and the P-type dopant used is CCl4 with a doping concentration of 0.5×10 18 cm -3 ~1×10 18 cm -3 ; Metal doped layer Al 0.5 In 0.5 The thickness of P:Mg is 10nm~20nm, the P-type dopant used is Cp2Mg, and the doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 .

[0055] (11) Growth of P-type transition layer: Set the temperature of the reaction chamber to 730±20℃, introduce TMGa, TMAl, TMIn, and PH3, and grow (Al) with a thickness of 10nm to 20nm. x4 Ga 1-x4 ) 0.5 In 0.5 P material, dopant is Cp2Mg, doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 , the value range of x4 is 0.3~0.4.

[0056] (12) Growth of P-type window layer: The reaction chamber temperature was set to 680±20°C, TMGa and PH3 were introduced, and GaP material with a thickness of 4000nm to 5000nm was grown. CP2Mg was used as the P-type dopant with a doping concentration of 2×10 18 cm -3 ~3×10 18 cm -3 ;

[0057] (13) Wafer removal: After the growth is completed, the temperature of the MOCVD reaction chamber is lowered to 110°C, and then the pressure is adjusted to 1000 mbar. The reaction chamber is opened and the epitaxial wafer is removed.

[0058] In order to further illustrate the present invention, the present invention is described in detail below in conjunction with specific embodiments.

[0059] Example 1

[0060] A method for preparing a red light LED epitaxial wafer comprises the following steps:

[0061] (1) The MOCVD was evacuated to 50 mbar in a pure H2 atmosphere, and the reaction chamber temperature was set to 400°C. The GaAs substrate was then transferred to the reaction chamber through a robot transfer bin, and then the temperature was rapidly raised to 750°C and maintained at 750°C for 10 min.

[0062] (2) Growth of GaAs buffer layer: The reaction chamber temperature was set to 700°C, TMGa and AsH3 were introduced, and a GaAs buffer layer material with a thickness of 200 nm was grown. SiH4 was used as an N-type dopant with a doping concentration of 3×10 18 cm -3 .

[0063] (3) Growth of oxidation-resistant DBR reflective layer: The reaction chamber temperature was set to 700°C, TMAl and AsH3 were introduced, SiH4 and DETe were introduced as N-type co-dopants, and AlAs material with a thickness of 45 nm was grown. The flow rate of SiH4 was set to 80 sccm, and the doping concentration was 2×10 18 cm -3 The flow rate of DETe was set to 20 sccm and the doping concentration was 0.5×10 18 cm -3 Then turn off DETe and introduce TMGa to grow Al with a thickness of 60nm. 0.4 Ga 0.6 As material, dopant is SiH4, doping concentration is 1×10 18 cm -3 The above co-doped AlAs and Al 0.4 Ga 0.6As growth combination forms the first oxidation resistant DBR reflective layer, and then the cycle 14 is repeated for the combined structure.

[0064] (4) Growth of N-type confinement layer: Set the reaction chamber temperature to 700°C, introduce TMAl, TMIn, and PH3, and grow an Al layer with a thickness of 300 nm. 0.5 In 0.5 P, doping concentration is 1×10 18 cm -3 , the N-type dopant is SiH4.

[0065] (5) Growth of N-side microstrain layer: Set the reaction chamber temperature to 700°C, introduce TMGa, TMAl, TMIn, and PH3, and grow AlGaInP material with a thickness of 40 nm. The total molar amount x+y of the molar amount of Al source x and the molar amount y of Ga source in the N-side microstrain layer is 140 μmol, and y=a*x, with a coefficient a of 0.07; the N-side microstrain layer is non-doped.

[0066] (6) Growth of N-side space layer: Set the reaction chamber temperature to 700°C, introduce TMGa, TMAl, TMIn, and PH3, and grow (Al) with a thickness of 50 nm. 0.7 Ga 0.3 ) 0.5 In 0.5 P material; the N-side space layer is undoped.

[0067] (7) Growth of multi-quantum well active layer: The reaction chamber temperature was set to 700°C, and TMGa, TMAl, TMIn, and PH3 were introduced to grow quantum well layers and quantum barrier layers, respectively (Al 0.06 Ga 0.94 ) 0.5 In 0.5 P、(Al 0.7 Ga 0.3 ) 0.5 In 0.5 P material, wherein the thickness of a single-layer quantum well is 6nm, and the thickness of a single-layer quantum barrier is 8nm; the number of periods is 30 pairs, and the light-emitting region is non-doped;

[0068] (8) Growth of P-side space layer: Set the temperature of the reaction chamber to 700°C, introduce TMGa, TMAl, TMIn, and PH3, and grow (Al) with a thickness of 50 nm. 0.7 Ga 0.3 ) 0.5 In0 .5 P material; the P side space layer is non-doped.

[0069] (9) Growth of P-side microstrain layer: Set the reaction chamber temperature to 700°C, introduce TMGa, TMAl, TMIn, and PH3, and grow AlGaInP material with a thickness of 40 nm. The total molar amount x+y of the molar amount of Al source x and the molar amount y of Ga source in the P-side microstrain layer is 140 μmol, and y=a*x, with a coefficient a of 0.07; the P-side microstrain layer is non-doped.

[0070] (10) Growth of P-type cyclic doping confinement layer: Set the temperature of the reaction chamber to 730°C, introduce TMAl, TMIn, and PH3 to grow Al 0.5 In 0.5 P material is used as P-type cyclic doping limiting layer. First organic doping and then metal doping, Al 0.5 In 0.5 P:C / Al 0.5 In 0.5 P:Mg alternately grows to form a cyclic doping confinement layer, and the number of pairs of cycles is 15. In a single cyclic doping structure, the organic doping layer Al 0.5 In 0.5 The thickness of P:C is 5nm, the P-type dopant used is CCl4, and the doping concentration is 0.5×10 18 cm -3 ; Metal doped layer Al 0.5 In 0.5 The thickness of P:Mg is 10nm, the P-type dopant used is Cp2Mg, and the doping concentration is 1×10 18 cm -3 .

[0071] (11) Growth of P-type transition layer: Set the reaction chamber temperature to 730°C, introduce TMGa, TMAl, TMIn, and PH3, and grow a 10nm thick (Al 0.3 Ga 0.7 ) 0.5 In 0.5 P material, dopant is Cp2Mg, doping concentration is 1×10 18 cm -3 .

[0072] (12) Growth of P-type window layer: The reaction chamber temperature was set to 680°C, TMGa and PH3 were introduced, and GaP material with a thickness of 4000 nm was grown. CP2Mg was used as the P-type dopant with a doping concentration of 2×10 18 cm -3 ;

[0073] (13) Wafer removal: After the growth is completed, the temperature of the MOCVD reaction chamber is lowered to 110°C, and then the pressure is adjusted to 1000 mbar. The reaction chamber is opened and the epitaxial wafer is removed.

[0074] Comparative Example 1

[0075] A conventional red LED epitaxial wafer is prepared by conventional methods, and its structural schematic diagram is shown in FIG. Figure 1 shown.

[0076] Test example

[0077] 1. After the red light LED obtained in Comparative Example 1 and the red light LED obtained in Example 1 were operated for 1000 hours in a high temperature (85°C) and high humidity (air humidity 85%) environment (operating current 10 mA), the chip state and the cut epitaxial structure layer inside the chip were observed using a scanning electron microscope. The results are as follows: Figure 3 to Figure 4 As shown, (a) is the SEM image of the LED appearance, and (b) is the SEM image of the LED internal cutting layer. Figure 3 The results show that conventional red LEDs oxidize when working in high temperature and high humidity environments. Adhesion anomalies and oxidation blackening can be seen on the surface of the epitaxial DBR reflective layer. By cutting the inside of the chip with FIB (focused ion beam) and observing the epitaxial structure layer, it can be clearly seen that lattice defects appear in the DBR reflective layer structure, resulting in chip reliability failure. Figure 4 It can be seen from the results that after the red light LED chip of the present invention has been operated for 1000 hours under the conditions of continuous high temperature, high humidity and high current, the epitaxial structure layer is clear and complete, and no oxidation anomalies or lattice defects occur.

[0078] 2. The red LED obtained in Example 1 and the red LED obtained in Comparative Example 1 were subjected to accelerated chip aging lighting test under high temperature (85°C) and high humidity (air humidity 85%) conditions, with a lighting current of 30 mA and a chip size of 110 μm×110 μm. The results are shown in Table 1. From the results in Table 1, it can be seen that after lighting for 168 hours, the brightness of the conventional red LED has decreased by 20.6%, and leakage has occurred. After 1000 hours, the brightness has decreased by 47.5%. However, after lighting for 1000 hours, the brightness of the red LED of the present invention has decreased by only 1.1%, and no leakage has occurred.

[0079] Table 1 High temperature continuous lighting chip brightness test results

[0080]

[0081] In summary, the present invention replaces the conventional DBR reflective layer material with an anti-oxidation DBR reflective layer doped with Si / Te, which can effectively prevent the DBR reflective layer of the red light LED from being oxidized by moisture in a humid environment, ensure the conductivity in a high temperature and high humidity environment, and avoid the problem of light efficiency attenuation; at the same time, Al is introduced into the P-type confinement layer. 0.5 In 0.5 P:C / Al0.5 In 0.5 The P:Mg periodic cyclic doping structure and the insertion of N-side / P-side micro-strain layer materials outside the space layers on both sides can effectively inhibit the diffusion of Mg elements into the light-emitting active area, solving the brightness attenuation problem of LED chips under high temperature, high humidity and high current density conditions, as well as after high temperature baking and reflow soldering during the packaging process. The resulting red light LED has high luminous efficiency and brightness, good reliability and stability, and is suitable for high temperature, high humidity and high current working conditions.

[0082] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A red light LED epitaxial wafer, characterized in that: The red light LED epitaxial wafer includes, from bottom to top, a GaAs substrate, a GaAs buffer layer, an anti-oxidation DBR reflective layer, an N-type confinement layer, an N-side micro-strain layer, an N-side space layer, a multi-quantum well active layer, a P-side space layer, a P-side micro-strain layer, a P-type cyclic doping confinement layer, a P-type transition layer, and a P-type window layer; The anti-oxidation DBR reflective layer is AlAs / Al x1 Ga 1-x1 As alternately grows in a periodic cycle structure, and in each pair of periodic cycle structures, AlAs is co-doped with Si / Te. x1 Ga 1-x1 As is doped with Si, where the value of x1 ranges from 0.4 to 0.6; The material of the P-type cyclic doping limiting layer is Al 0.5 In 0.5 P, the cyclic doping method is to first dope organically and then dope metals to form Al 0.5 In 0.5 P:C / Al 0.5 In 0.5 The periodic cyclic doping structure composed of P:Mg alternating growth has a cycle number of 10 to 15 pairs; The materials of the N-side microstrain layer and the P-side microstrain layer are both AlGaInP, and are both undoped. The molar amount of the Al source material is x, and the molar amount of the Ga source material is y, wherein the total molar amount x+y of x and y is 140μmol~150μmol, and y=a*x, and the coefficient a is 0.

07.

2. A red LED epitaxial wafer according to claim 1, characterized in that: In the Si / Te co-doped anti-oxidation DBR reflective layer AlAs material, the Si dopant is SiH4 with a doping concentration of 2×10 18 cm -3 ~3×10 18 cm -3 ; The dopant of Te is DETe, and the doping concentration is 0.5×10 18 cm -3 ~1×10 18 cm -3 ;Al x1 Ga 1-x1 In As material, the dopant of Si is SiH4, and the doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 .

3. A red LED epitaxial wafer according to claim 1, characterized in that: In each pair of periodic doping structures, Al 0.5 In 0.5 The organic dopant used in P:C is CCl4, and the doping concentration is 0.5×10 18 cm -3 ~1×10 18 cm -3 , thickness is 5nm~10nm; Al 0.5 In 0.5 The metal dopant used in P:Mg is Cp2Mg, and the doping concentration is 1×10 18 cm -3 ~2×10 18 cm -3 , thickness is 10nm~20nm.

4. A red LED epitaxial wafer according to claim 1, characterized in that: The thickness of the N-side micro-strain layer is 40nm-60nm, and the thickness of the P-side micro-strain layer is 70nm-90nm.

5. A method for preparing a red LED epitaxial wafer according to any one of claims 1 to 4, characterized in that: Using MOCVD equipment, a GaAs buffer layer, an anti-oxidation DBR reflective layer, an N-type confinement layer, an N-side micro-strain layer, an N-side space layer, a multi-quantum well active layer, a P-side space layer, a P-side micro-strain layer, a P-type cyclically doped confinement layer, a P-type transition layer, and a P-type window layer are sequentially grown on a GaAs substrate; When the anti-oxidation DBR reflective layer is grown, Si / Te co-doped AlAs material is first grown, and then Si-doped AlGaAs material is grown to complete the first anti-oxidation DBR reflective layer, and then 14 to 19 pairs of growth cycles are repeated; When the P-type cyclic doping restriction layer grows, the organic doping layer Al is first grown. 0.5 In 0.5 P:C, then grow the metal doping layer Al 0.5 In 0.5 P:Mg forms the first pair of cyclic doping confinement layers, and then the cycle is repeated to grow 9 to 14 pairs.

6. The method for preparing a red LED epitaxial wafer according to claim 5, characterized in that: The growth steps of the anti-oxidation DBR reflective layer are as follows: setting the temperature of the reaction chamber to 700±20°C, introducing TMAl, AsH3, SiH4 and DETe as dopants on the GaAs buffer layer, growing AlAs material with a thickness of 45nm-50nm, wherein the set flow rate of SiH4 is 80sccm-110sccm, the set flow rate of DETe is 20sccm-40sccm, then turning off DETe, introducing TMGa and SiH4 as dopants, and growing AlAs with a thickness of 60nm-65nm. x1 Ga 1-x1 As material, and then repeated cycle growth AlAs / Al x1 Ga 1-x1 As, where the value range of x1 is 0.4 to 0.

6.

7. The method for preparing a red LED epitaxial wafer according to claim 5, characterized in that: The growth steps of the N-side microstrain layer and the P-side microstrain layer are the same: setting the reaction chamber temperature to 700±20°C, introducing TMAl, TMGa, TMIn, and PH3 into the N-type confinement layer or the P-side space layer to grow AlGaInP material, the molar amounts of the Al source material and the Ga source material are x and y, respectively, wherein the total molar amount x+y of x and y is 140μmol~150μmol, and y=a*x, and the coefficient a is 0.

07.

8. The method for preparing a red LED epitaxial wafer according to claim 5, characterized in that: The P-type cyclic doping restriction layer growth step is: setting the reaction chamber temperature to 730±20° C., introducing TMAl, TMIn, and PH3 into the P-side micro-strain layer, and growing Al 0.5 In 0.5 P material, CCl4 is used as the dopant of the organic doping layer, the flow rate is set to 5sccm~10sccm, then CCl4 is turned off, Cp2Mg is introduced as the dopant of the metal doping layer, the flow rate is set to 60sccm~80sccm, and the cycle is repeated to grow Al 0.5 In 0.5 P:C / Al 0.5 In 0.5 P:Mg.

Citation Information

Patent Citations

  • Light emitting diode having distributed Bragg reflector with modulation doping structure

    CN102427105A

  • Positive polarity infrared LED epitaxial structure and preparation method thereof

    CN118919623A